Improving drug delivery to the lungs as a function of excipient choice - Olubi, Rebecca (2024)
Drug delivery to the lungs remains an attractive target for the administration of local as well as systemic therapies. Recent developments in pulmonary drug delivery have been centred around advancing and improving drug delivery devices. However, other challenges persist such as the limited range of approved excipients for inhaled formulations. A review of the FDA inactive ingredients database (IID) revealed that only 18% (63 excipients) appear on the FDAapproved drug products currently marketed for delivery by inhalation. The limited range of excipients poses a challenge in tailoring inhaled formulations to meet the complex therapeutic demands for managing respiratory diseases. Even for existing excipients with well characterised safety profiles, there are still ongoing endeavours to understand the interaction between excipients and Active Pharmaceutical Ingredients (APIs). However, the majority of these studies have been focused on transporter systems in the gastrointestinal tract which may not be representative of the respiratory system. Therefore, the aim of this project was to provide a better understanding of the effects of excipients on inhaled drug before, during, and after administration. The investigations of this study were performed using budesonide inhalation suspension (BIS) as a model. BIS contains micronized budesonide as the API and polysorbate 80 as the stabilizing excipient.